Hubungan Angka Kecelakaan Kerja dengan Tingkat Pemenuhan Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja - Gerry Silaban (Berita Kedokteran Masyarakat (BKM), 2009)
Background: The existing of opinion that enterprises registered within Employment Accident Benefit Program to reduce the employment’s accident risk will disregard the implementation of occupational health and safety (OHS). The implementation of OHS through the occupational health and safety management system (OHSMS) is an obligation for enterprises as means to prevent employment accident in order to establish a comfort, health and safe workplace and contiunity of business.Method: The type research which used is survey research using cross-sectional design. Samples consist of 55 enterprises from type III of group-business which registered in Employment Accident Benefit Program at PT Jamsostek Medan Branch. Accident rate data were gathered through enterprises report on Jamsostek Form 3 Type K.K.3 (Employment Accident Report Phase I) within one year period (January 1st - December 31st, 2005). The level of compliance the implementation of OHSMS was measured by OHSMS audits which consist of 166 criteria. Regression analyzes was employed to examine relationship between accident rate and level of compliance the implementation of OHSMS.Results: Accident rate was varying among each business types ranges 87 cases as most frequent and 1 case least. Higher level of compliance the implementation of OHSMS were 127 criteria (76.51%), lowest were 6 criteria (3.61%) with average     32 criteria (19.04%). It is recognized that 2 (3.64%) enterprises were reach 60 - 84% criteria and 53 (96.36%) enterprises reach 0 - 60% criteria for compliance. Total average and percentage which actually been comply by enterprises on each criteria element from 12 auditing elements of OHSMS was mostly on 5th element (purchasing). Relationship between accident rate and level of compliance the implementation of OHSMS is significant (p < 0.05) with correlation coefficient r = - 0.236.Conclusion: Management must have solid commitment and entail every worker to implement OHSMS, and involves various relevant and qualify parties thus level of compliance the implementation of OHSMS can be improved and reducing accident rate.Keywords:  registered enterprises in the employment accident benefit program, accident rate, the level of compliance the implementation of occupational health and safety management system